Full-Scale Assessment of the “5GT System” for Tracking and Monitoring of Multimodal Dry Containers - Mariano Falcitelli; Sandro Noto; Paolo Pagano; Molka Gharbaoui; Agostino Isca; Francesco Fresi; Antonio Mancina; Massimo Toffetti; Antonio Amatruda; Nicola Bendoni; Emanuele Sarandrea; Paolo Scalambro (IoT)
A novel tracking and monitoring system for ISO 668 dry containers was realized by the ESA-funded “5G SENSOR@SEA” project, integrating 5G cellular technologies for massive Internet of Things with a GEO satellite-optimized backhauling link. The scope is the development of monitoring and tracking new services for multimodal container shipping. With the cooperation of four industrial partners and a telecommunication research center, the so-called “5GT System” was designed, developed, tested and validated up to field trials. Several modules of the system were designed, built and finally installed on the ship and in the teleport: the container tracking devices placed on the containers, the NB-IoT cellular network with optimized satellite backhauling, the Ku-band satellite terminals and the maritime service platform based on the OneM2M standard. The field trial conducted during the intercontinental liner voyage of a container ship showed primary technical achievements, including fair switching between terrestrial and satellite networks, reduction in packet loss in the open sea scenario and seamless integration of the BLE mesh network over the container tracking devices as NB-IoT/BLE LE Mesh gateways.